2015
DOI: 10.1080/15567265.2015.1027836
|View full text |Cite
|
Sign up to set email alerts
|

Near-Field Thermal Radiation: Recent Progress and Outlook

Abstract: Any materials at temperatures higher than absolute zero emit electromagnetic waves due to the thermal fluctuations of free charges or ions. When two or more bodies at different temperatures are brought sufficiently close to each other with vacuum gap spacing smaller than the characteristic thermal wavelength, near-field radiative heat flux can exceed the far-field blackbody limit, governed by the well-known Stefan-Boltzmann law, by orders of magnitude. This article reviews the recent progress on both theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
65
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(65 citation statements)
references
References 172 publications
(267 reference statements)
0
65
0
Order By: Relevance
“…Examples include surface phonon polaritons that can exist at the surface of polar dielectric materials such as SiO 2 and SiC, or surface plasmon polaritons (SPPs) that can be supported between metallic surfaces or structures [13][14][15][16][17]. Recently, it is demonstrated that surface plasmons in graphene can also achieve a similar role to enhance the photon tunneling between two graphene sheets [18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Examples include surface phonon polaritons that can exist at the surface of polar dielectric materials such as SiO 2 and SiC, or surface plasmon polaritons (SPPs) that can be supported between metallic surfaces or structures [13][14][15][16][17]. Recently, it is demonstrated that surface plasmons in graphene can also achieve a similar role to enhance the photon tunneling between two graphene sheets [18].…”
Section: Introductionmentioning
confidence: 99%
“…This is the so-called photon tunneling and the resulted nearfield heat transfer rate can be orders of magnitude larger compared to the blackbody limit [6][7][8][9][10][11][12]. The enhanced radiative heat transfer finds numerous applications such as thermal energy harvesting, radiative cooling, and thermal imaging [2]. Continuous efforts have been devoted to exploring new materials or structures that can result in large heat transfer rates that can benefit these applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A selection of more recent reviews are [5][6][7][8][9][10][11][12][13]. The main idea may be explained by analogy to Brownian motion: instead of characterizing the motion of a particle by its thermal energy, one introduces microscopic trajectories that are perturbed by randomly fluctuating forces.…”
Section: Introduction: Motivationmentioning
confidence: 99%
“…Moreover, a number of numerical methods have been adapted to near-field thermal radiation: the finite-difference time-domain method [37][38][39], the finite-difference frequencydomain method [40], the boundary element method [41], the method of moments [42] and the discrete dipole approximation, which has been referred to as the thermal discrete dipole approximation (T-DDA) [43,44]. Additional information about near-field thermal radiation modeling and its potential engineering applications can be found in the numerous review papers published during the past decade [28,[45][46][47][48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%